Local Associations and Global Reason: Fodor’s Frame Problem and Second-Order Search - Clark, Andy (Hermes-Lavoisier, Paris & Oxford., 2002)
Kleinberg (1999) describes a novel procedure for efficient search in a dense hyper-linked environment, such as the world wide web. The procedure exploits information implicit in the links between pages so as to identify patterns of connectivity indicative of “authorative sources”. At a more general level, the trick is to use this second-order link-structure information to rapidly and cheaply identify the knowledge-structures most likely to be relevant given a specific input. I shall argue that Kleinberg’s procedure is suggestive of a new, viable, and neuroscientifically plausible solution to at least (one incarnation of) the so-called “Frame Problem” in cognitive science viz the problem of explaining global abductive inference. More accurately, I shall argue that Kleinberg’s procedure suggests a new variety of “fast and frugal heuristic” (Gigerenzer and Todd (1999)) capable of pressing maximum utility from the vast bodies of information and associations commanded by the biological brain. The paper thus takes up the challenge laid down by Fodor ((1983)(Ms)). Fodor depicts the problem of global knowledge-based reason as the point source of many paradigmatic failings of contemporary computational theories of mind. These failings, Fodor goes on to argue, cannot be remedied by any simple appeal to alternative (e.g. connectionist) modes of encoding and processing. I shall show, however, that connectionist models can provide for one neurologically plausible incarnation of Kleinberg’s procedure. The paper ends by noting that current commercial applications increasingly confront the kinds of challenge (such as managing complexity and making efficient use of vast data-bases) initially posed to biological thought and reason.
Keywords: Philosophy